An interrelation of physical working capacity and body component composition indicators of amateur athletes - Zoya Gorenko; Boris Ocheretko; Antonina Kovelskaya (Kharkiv State Academy of Physical Culture, 2017)
Purpose: determine the features of the body component composition and the level of physical performance, as well as the structure of the correlation between these indicators in amateur athletes. Material & Methods: in conditions of the test with physical load with stepwise increasing power in the 71-st physically active person, the reaction of the cardio-respiratory system to physical activity. The body component composition was determined by the bioelectrical impedance method. Result: in amateur athletes, the relative VO2max and power ratings are positively correlated with the relative body water content and have a negative relationship with age, body weight, body mass index, fat content. Oxygen pulse with a high degree of probability positively correlated with body weight, body mass index, metabolic rate, fat-free mass, water content and predictable muscle mass in all body segments. Conclusion: Conducted studies indicate a sufficient level of aerobic capacity, overall performance, the efficiency of the cardiac cycle, the functioning of the О2-transport system and skeletal muscles ability to absorb oxygen from the amateur athletes, and excess fat tissue negatively affects physical performance, overall endurance and achieving high sports results in sports on the endurance.